Prevention practice in primary care - Gorin, Sherri Sheinfeld ([Oxford] : Oxford University Press, 2014)
This volume systematically explores state-of-the-art practical approaches to effective prevention in primary care. Guided by theory and evidence, the book reviews approaches to risk factor identification and modification for the major causes of mortality in adulthood, including cancer, stroke, and cardiovascular disease.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Preventive health services; Primary health care